Health Promotion Media Intervention Towards Balanced Nutrition Knowledge to Increase Immunity in Inspired Families in Uteunkot Village, Lhokseumawe City - Novalia, Vera; Utariningsih, Wheny; Zara, Noviana; Meutia, Zahra; Imanda, Fetty (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2024)
Nutritional problems are a health problem because the morbidity rate is very high throughout the world, including Indonesia, which has complex nutritional problems, namely stunting, wasting, and overweight. Data in Lhokseumawe City shows that the percentage of malnutrition among toddlers aged 0-59 months is 5.2%; short or very short, often known as stunting, has a percentage of 3.9%; underweight or very thin toddlers have a percentage of 3.4%. So, it is necessary to increase body immunity through health promotion media. This research aims to determine Health Promotion Media on Knowledge of Balanced Nutrition to Increase Body Immunity in Assisted Families for 150 respondents. The research method used is quasi-experimental, using a one-group pretest-posttest design. Data was collected using a questionnaire sheet. The research results showed that the characteristics of most respondents in the age group were 59 (39.3%). The research results showed an increase in knowledge to 96.7% in the excellent category after the intervention. The use of audiovisual media influences knowledge based on the Wilcoxon test with a p-value of 0.000. This research concludes that there is an influence of audiovisual media on knowledge about balanced nutrition to increase immunity in the Uteunkot village community